Identification of Chaoborus kairomone chemicals that induce defences in Daphnia. (December 2018) - Weiss, Linda; Albada, Bauke; Becker, Sina; Meckelmann, Sven; Klein, Julia; Meyer, Martin; Schmitz, Oliver; Sommer, Ulf; Leo, Markus; Zagermann, Johannes; Metzler-Nolte, Nils; Tollrian, Ralph
Abstract Infochemicals play important roles in aquatic ecosystems. They even modify food web interactions, such as by inducing defenses in prey. In one classic but still not fully understood example, the planktonic freshwater crustaceanDaphnia pulex forms specific morphological defenses (neckteeth) induced by chemical cues (kairomones) released from its predator, the phantom midge larvaChaoborus . On the basis of liquid chromatography, mass spectrometry, and chemical synthesis, we report here the chemical identity of theChaoborus kairomone. The biologically active cues consist of fatty acids conjugated to the amino group of glutamine via the N terminus. These cues are involved inChaoborus digestive processes, which explains why they are consistently released despite the disadvantage for its emitter. The identification of the kairomone may allow in-depth studies on multiple aspects of this inducible defense system. The freshwater microcrustaceanDaphnia pulex forms defensive neckteeth in response to a collection of chemical cues (the kairomone), now identified as certain fatty acids conjugated to glutamine, released during digestion by its predatorChaoborus .